Formation of speech activity in teaching foreign languages to junior school students - Abilgaziyeva, Zh. K.; Janzakova, Sh. I.; Nurgaliyeva, S.A.; Seitimbetova, S.D. (Opción, 2019)
The article is devoted to the formation of speech activity among junior school students in the process of teaching foreign languages. This study follows a general methodological basis for learning, which characterizes the point of view on the subject of learning and the possibility of mastering it in the learning process. As a conclusion, prospects for the study are seen in the use of an integrative approach during the teaching of foreign languages to the junior school students when the teacher develops a work curriculum, in training and retraining programs for primary school and foreign language teachers.